PENGEMBANGAN LAGU DAERAH SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN PANCASILA UNTUK MENUMBUHKAN MOTIVASI BELAJAR SISWA - Ferdisa Remalya Putri; Cicilia Ika Rahayu Nita; Andika Gutama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a regional song-based learning media using the song “Lir-Ilir” for Pancasila Education in Grade III students at SDN Semen 04, especially in Chapter 4 “Let’s Get to Know Pancasila”. The research applied the Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The developed product was validated by media experts, material experts, and language experts to determine its feasibility. Practicality was measured through teacher responses, while effectiveness was evaluated using student motivation questionnaires administered before (pre-test) and after (post-test) the implementation. The results showed that the media feasibility was categorized as very feasible, with validation scores from media experts at 95%, material experts at 87.5%, and language experts at 91.67%. The practicality test also indicated a very practical category with a teacher response score of 99.23%. Furthermore, student motivation increased significantly after using the media, as shown by improvements in indicators of interest, learning enthusiasm, concentration, activeness, and learning responses. Therefore, the “Lir-Ilir” regional song-based learning media is considered feasible, practical, and effective in improving students’ learning motivation in Pancasila Education.